Effect of Foot-Planting Strategy on Anterior Cruciate Ligament Loading in Women During a Direction Diversion Maneuver: A Musculoskeletal Modeling Approach. Issue 11 (19th November 2020) - Lee, Jusung; Pathak, Prabhat; Panday, Siddhartha Bikram; Moon, Jeheon
Background: Although there is a higher prevalence of noncontact anterior cruciate ligament (ACL) injuries during a direction diversion maneuver (DDM), no previous studies have reported how foot-planting strategies affect ACL loading. Purpose: To investigate the effect of foot-planting strategies on ACL loading in women during a DDM task using a musculoskeletal modeling approach. Study Design: Descriptive laboratory study. Methods: A total of 13 female participants performed a DDM task, which involved running at 4.5 ± 0.2 m/s and turning left at 35° to 55° under a foot-planting strategy in 3 directions: neutral, toe-in, and toe-out. Kinematic and kinetic data were measured with the use of a 3-dimensional motion capture system and force platform to calculate variables such as joint angle, shear force, and moment. Anterior ACL and posterior ACL forces were extracted using musculoskeletal modeling. Results: The peak anterior ACL force was significantly larger for the toe-out condition (31.29 ± 4.02 N/body weight [BW]) compared with the toe-in condition (25.43 ± 5.68 N/BW) ( P = .047), with no significant difference in the neutral condition. The toe-out condition had a higher knee valgus angle (2.98° ± 4.20°; P = .041), knee shear force (10.20 ± 1.69 N/BW; P = .009), and knee internal rotation moment (–0.18 ± 0.16 N·m/BW×height; P = .012) than the toe-in and neutral conditions. Conclusion: Through musculoskeletal modeling, we were able to conclude that the toe-out condition during the DDM might result in a higher risk of ACL injuries. Athletes and sports practitioners should avoid the toe-out foot-planting strategy when participating in a sporting activity. Clinical Relevance: Based on these findings, medical professionals and athletic coaches can gain knowledge on how foot-planting strategy affects ACL loading. Understanding the actual cause of an ACL injury can be useful for designing preventive training programs or strategies to decrease the risk of such injuries.